An updated Checklist of the Mediterranean fishes of Israel, with illustrations of recently recorded species and delineation of Lessepsian migrants - Golani, Daniel (Zootaxa, 2021)
This checklist of the Mediterranean fishes of Israel enumerates 469 species which is an addition of 62 species since the previous checklist of 2005. This new checklist includes 58 Condrichthys and 411 Osteicthys species. Most newly-recorded species are of Red Sea origin (Lessepsian migrants)—38 species, 25 species are from previously poorly investigated habitats, mainly deep water, while two species reached the Mediterranean most likely by ballast water and two are aquaculture escapees. The dramatic increase in the number of Lessepsian migrants (an average of 2.5 species per year) is most likely due to the increased water influx between the Red Sea and the Mediterranean, following the recent opening of the new parallel, 72 km, “new canal” and the enlargement of other parts of the Suez Canal.